Chromosome Instability and Mosaic Aneuploidy in Neurodegenerative and Neurodevelopmental Disorders - Potter, Huntington; Chial, Heidi J.; Caneus, Julbert; Elos, Mihret; Elder, Nina; Borysov, Sergiy; Granic, Antoneta (Frontiers in Genetics, 2019)
Evidence from multiple laboratories has accumulated to show that mosaic neuronal aneuploidy and consequent apoptosis characterizes and may underlie neuronal loss in many neurodegenerative diseases, particularly Alzheimer’s disease and frontotemporal dementia. Furthermore, several neurodevelopmental disorders, including Seckel syndrome, ataxia telangiectasia, Nijmegen breakage syndrome, Niemann-Pick type C, and Down syndrome, have been shown to also exhibit mosaic aneuploidy in neurons in the brain and in other cells throughout the body. Together, these results indicate that both neurodegenerative and neurodevelopmental disorders with apparently different pathogenic causes share a cell cycle defect that leads to mosaic aneuploidy in many cell types. When such mosaic aneuploidy arises in neurons in the brain, it promotes apoptosis and may at least partly underlie the cognitive deficits that characterize the neurological symptoms of these disorders. These findings have implications for both diagnosis and treatment/prevention.